Fluorescence Chemosensors for Chemical Warfare Agent Mimic Diethylcyanophosphonate Via Co2+‐Naphthalimide Based Nanoaggregate in Aqueous Medium. Issue 17 (13th June 2017) - Raj, Pushap; Singh, Narinder
Abstract: Two new Naphthalimide based dipodal receptors K1 and K2 has been synthesized and selectively formed upon complexation with cobalt ion. Further, these cobalt complexes (K1.Co 2+ and K2.Co 2+ ) were fabricated to nanoaggregate in aqueous medium. The stability of these nanoaggregates was established with DLS, TEM, AFM and emission spectroscopy. The nanoaggregates N1‐N2 were utilized to selectively sensing of diethylcyanophosphonate in aqueous medium. The nanoaggregate N1 and N2 exhibit 2 fold enhancement in the emission spectrum in presence of Diethylcyanophosphonate (DECP) which is due to rigidity induced fluorescent enhancement. The detection limit to be achieved for DECP is 21 nM in aqueous medium. Additionally, the solution coated filter paper strip of nanoaggregate N1 can detect DECP, thus providing very simple and low coast sensing kit for DECP. Abstract : The cobalt complexes of naphthalimide based receptor have been synthesized and their aggregate formation was prepared in water via re‐precipitation method. Moreover, these aggregate were utilize for the selective sensing of toxic diethylcyanophosphonate in aqueous medium. Both colorimetric and fluorometric method was used to confirm their binding behavior. The paper based sensor strip has been successfully developed for detection of DECP. The lowest detection limit of 21 nM can be achieved.